PENGARUH HARGA DAN PENATAAN PRODUK (DISPLAY)TERHADAP KEPUTUSAN PEMBELIAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA UD. REJEKI AGUNG LAMONGAN - azar, Moh. Azus; Yudiarto, Eko (J-MACC : journal of management and accounting, 2019)
This research was conducted at UD. REJEKI AGUNG Lamongan is engaged in marketing children's toys. The purpose of this study was to determine how the influence of displays on purchasing decisions with customer satisfaction as an intervening variable at UD. REJEKI AGUNG Lamongan. The purpose of this study was to determine how much influence the display (product arrangement) on purchasing decisions with consumer satisfaction as an intervening variable. The population in this study were all consumers who had purchased the product in 2017. While the sample was 98 respondents using the Convinience Sampling method, which is a sampling technique that is easy to find. The results of this study indicate that the price and display partially affect Consumer satisfaction and Purchasing Decisions. And simultaneously also shows that price and display influences consumer satisfaction and purchasing decisions. Price variables give a greater influence on customer satisfaction and purchasing decisions.